Coping mechanisms of families of children’s with special education needs - Enache, Rodica Gabriela; Mitu, Iuliana (Technium Social Sciences Journal, 2022)
The issues of disabilities in their children shake the families and serve as sources of severe psychological disruption to family adjustment. The parents of children with special needs are confronted with major changes in their family life, both with regard to the relationship between husbands, as well as to the parent-child relationship and for this efficient relationship and their quality of life not to suffer, it is necessary that each of the parents develops his/her own resources. The parents of such children live with many difficult issues and frequently experience trauma, grief and stress.